Cyberstalking: Investigating formal intervention and the role of Corporate Social Responsibility. Issue 4 (July 2017) - al-Khateeb, Haider M.; Epiphaniou, Gregory; Alhaboby, Zhraa A.; Barnes, James; Short, Emma
Highlights: Cyberstalking often occurs on private channels such as emails and mobile text/calls. 41.6% avoid police due to fear of escalation, guilt/sympathy and self-blaming. Lack of support offered by service providers is a Corporate Social Irresponsibility. Victims prefer third-party intervention to mitigate associated risks. Public awareness should be raised on service providers' liability. Abstract: Context: Online harassment and stalking have been identified with growing accordance as anti-social behaviours, potentially with extreme consequences including indirect or direct physical injury, emotional distress and/or financial loss. Objective: As part of our ongoing work to research and establish better understanding of cyberstalking, this study aims to investigate the role of Police, Mobile Operators, Internet Service Providers (ISPs) and owners/administrators of online platforms (e.g. websites, chatrooms) in terms of intervention in response to offences. We ask to what different authorities do people report incidents of cyberstalking? Do these authorities provide satisfactory responses or interventions? And how can this be improved? Furthermore, we discuss the role of Corporate Social Responsibility (CSR) to encourage the implementation of cyberstalking-aware schemes by service providers to support victims. In addition, CSR can be used as a means to measure the effects of externality factor in dictating the relationship between the impact of a given individuals' privacy loss and strategic decisions on investment to security controls in an organisational context. Method: A mixed method design has been used in this study. Data collection took place by means of an online survey made available for three years to record both qualitative and quantitative data. Overall, 305 participants responded from which 274 identified themselves as victims of online harassment. Result: Our results suggest that most offences were communicated through private channels such as emails and/or mobile texts/calls. A significant number of victims did not report this to their service provider because they did not know they could. While Police were recognised as the first-point-of-contact in such cases, 41.6% of our sample did not contact the Police due to reasons such as fear of escalation, guilt/sympathy and self-blaming. Experiences from those who have reported offences to service providers demonstrate that no or very little support was offered. Overall, the majority of participants shared the view that third-party intervention is required on their behalf in order to mitigate risks associated with cyberstalking. An independent specialist anti-stalking organisation was a popular choice to act on their behalf followed by the Police and network providers. Conclusion: Incidents are taking place on channels owned and controlled by large, cross-border international companies providing mobile services, webmail and social networking. The lack of support offered to victims in many cases of cyberstalking can be identified as Corporate Social Irresponsibility (CSI). We anticipate that awareness should be raised as regarding service providers' liability and social responsibility towards adopting better strategies.